2009
DOI: 10.1097/fbp.0b013e32832c7098
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effect of noradrenaline microinjection into the dorsal periaqueductal gray of rats

Abstract: The brain noradrenergic system has been implicated in the expression of defensive behaviors elicited by acute stress. The dorsal periaqueductal gray area (dPAG) is a key structure involved in the behavioral and cardiovascular responses elicited by fear and anxiety situations. Although there are noradrenergic terminals in the dPAG, few studies have investigated the role of noradrenaline (NA) in the dPAG on anxiety modulation. The aim of this study was to evaluate the effect of NA microinjection into the dPAG of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…According to Płaźnik et al [42] , intra-accumbens injection of NA or dopamine increased the rat rearing and locomotor activity in the open filed test. However, another study that used NA microinjection has shown no increase in the exploratory activity [43] . This contrast of results is probably attributed to the site of NA injection or the type of rearing activity recorded.…”
Section: Discussionmentioning
confidence: 99%
“…According to Płaźnik et al [42] , intra-accumbens injection of NA or dopamine increased the rat rearing and locomotor activity in the open filed test. However, another study that used NA microinjection has shown no increase in the exploratory activity [43] . This contrast of results is probably attributed to the site of NA injection or the type of rearing activity recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Adra1a , an alpha adrenergic receptor subunit gene, also had decreased expression. Because norepinephrine injected into the PAG has an anxiolytic effect (Pelosi et al., ), the decrease in Adra1a could make these animals more prone to anxiety in stressful situations.…”
Section: Discussionmentioning
confidence: 99%
“…The periaqueductal gray receives light projections from the vestibular nuclei [112], is connected reciprocally with the locus coeruleus [113], [114], and projects to the medial and lateral parabrachial nuclei [115]. Recent studies in rats indicate that Fos activation in locus coeruleus and the periaqueductal gray is observed in animals displaying escape responses in an elevated T-maze task [116], which may include recruitment of anxiolytic effects of norepinephrine via the dorsal periaqueductal gray [117].…”
Section: Discussionmentioning
confidence: 99%